LANGUAGE PROBLEMS IN APPLIED LINGUISTICS: LIMITING THE SCOPE - A. Effendi Kadarisman (TEFLIN Journal: A publication on the teaching and learning of English, 2014)
Â This article critically discusses the paradigmatic shift in applied linguistics, resulting in a claim that countless real-world language problems fall within its scope, but in reality they weaken the discipline and make it lack a focus. Then it takes a closer look at the nature of these language problems, and picks out, for analysis, real examples of writing problems in ELT in Indonesian context. It further argues that, by focusing primarily on problems in ELT and SLA, applied linguistics reaffirms its well-defined position and underscores its significant contributions to both disciplines. Finally, it concludes the discussion by adding some notes on the question of autonomy in both applied linguistics and in ELT in Indonesia.Â